Aluminum Detoxification by Humic Substance Extracted from Compost of Organic Wastes - Sugeng Winarso; Eko Handayanto; Abdullah Taufiq (JOURNAL OF TROPICAL SOILS, 2010)
Aluminum Detoxification by Humic Substance Extracted from Compost of Organic Wastes (S Winarso, E Handayanto and A Taufiq):  Humic substance could control the activity of metal as well as exchangeable aluminum (Alexch) on acid soil. The humic substance extracted from compost of agricultural waste is rarely conducted. The objective of research was to evaluate the effect of humic substance concentration and sources to pH and Al suspension. The research had been conducted in the Soil Laboratory of Agricultural Faculty of Jember University from April to July 2009. The humic substance used in these researches was extracted from compost of rice straw (RS), soybean straw (SS), cassava starch solid waste (CSSW), and empty bunch of oil palm tree (EBOPT). The humic substance concentration treatments were 0, 10, 20, 30, 40, 50, 75, 100, 150, 200, 250, and 300 ppm. Result of the analysis showed that characteristic of humic substance was difference depending on the source material used. The humic substance extracted from SS contain total base cations (K, Na, Ca, Mg) higher (1.17%) compared with CSSW (1.07%), OPT  (0.87%), and RS (0.69%). While the humic substances extracted from RS contain total organic acid (Acetic, Fumeric, cetoglutamic, Sucsinic, Propionic, Butiric, Ocsalic, and sitric acid) higher (157 ppm) compared with EBOPT (129 ppm), SS (115%), and CSSW (108%). Among these organic acids, acetic acid was highest concentration (> 34.51% of total acid). The addition of humic substance increased pH and decreased aluminum concentration of the suspension. The higher pH increment and Al concentration reduction took placed in the suspension treated with humic substance from SS compost. The correlation between decreasing Al concentration with humic substance concentration which explained chelation was higher (r = 0.97) than decreasing Al concentration with increasing pH which explained precipitation (r = 0.93). Based on these research results, it can be concluded that humic substance extracted from agricultural waste have a good prospect as a soil ameliorant to increase soil pH, detoxify soil aluminum, and increase soil P availability on acid soil.